(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2022)
The article describes those steps that came before the making of the 2004 documentary Alessandro Fersen. Being on Stage, contextualizes the project in itself and the event where it was screened for the first time. The article discusses why some materials were chosen and how those materials became part of a video storytelling, instead of an exhibit, or a more traditional essay. The main attempt is addressing the process of re-use of existing documents inside the documentary (photos, books, theatrical sketches, audio and video recordings and so on, from Museo Biblioteca dell’Attore di Genova, RAIteche, private archives). The documentary is now available in Italian on the Siena University YouTube channel and with English subtitles on the Columbia College Chicago website. Alessandro Fersen. Being on Stageis an example of documentation’s reworking and source enhancement, following a scientific concept of performative intertextual documentation.